Respostas
respondido por:
0
Resposta:
An = a1 + ( n-1) .r
An = 25 + ( 25 -1 ) . 6
An = 169
R = Razao
An = o termo em questao
A1 = primeiro termo
n = posiçao do termo em questao
Explicação passo-a-passo:
respondido por:
1
Explicação passo-a-passo:
- progressão aritmética >>>>>>>>
an = a1 + ( n - 1 ) . r
a1 = 25
n = 25
r = a2 - a1 >>> r = 31 - 25 = 6
a25 = 25 + ( 25 - 1 ) . 6
a25 = 25 + 24 . 6
a25 = 25 + 144
a25 = 169 <<<<<<<<<<<<<<< RESPOSTA
att: S.S °^°
Perguntas similares
4 anos atrás
4 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás